2020
DOI: 10.3390/healthcare8020180
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insight into How Nurses Working at PH Specialist Clinics in Sweden Perceive Their Work

Abstract: Outpatient pulmonary hypertension (PH) specialist centers have an important role in the optimal management of pulmonary arterial hypertension (PAH) and chronic thromboembolic pulmonary hypertension (CTEPH). The aim of the present study was to gain an understanding of the work facing nurses at the outpatient PH specialist centers in Sweden. All nurses (n = 14) working at the outpatient PH specialist centers in Sweden were included. Qualitative content analysis was employed to analyze the interviews, wherein an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…28 The present study showed that patients and spouses appreciated being seen at a PH specialist clinic, whose purpose is to provides good holistic care including treatment, support, and accurate information about the disease in a multi-professional environment. 4,29 Despite the changes and challenges a chronic disease infer on life, patients and spouses adapt and it might even strengthen a relationship. 30 The present study supports this by showing that even with a grim diagnosis as PAH or CTEPH, patients, and the spouses shared a feeling of relief that the search was over.…”
Section: Discussionmentioning
confidence: 99%
“…28 The present study showed that patients and spouses appreciated being seen at a PH specialist clinic, whose purpose is to provides good holistic care including treatment, support, and accurate information about the disease in a multi-professional environment. 4,29 Despite the changes and challenges a chronic disease infer on life, patients and spouses adapt and it might even strengthen a relationship. 30 The present study supports this by showing that even with a grim diagnosis as PAH or CTEPH, patients, and the spouses shared a feeling of relief that the search was over.…”
Section: Discussionmentioning
confidence: 99%